Snapshots of lymphatic pathways in colorectal cancer surgery using near-infrared fluorescence, in vivo and ex vivo. Issue 12 (December 2021) - Sato, Yu; Satoyoshi, Tetsuta; Okita, Kenji; Kyuno, Daisuke; Hamabe, Atsushi; Okuya, Koichi; Nishidate, Toshihiko; Akizuki, Emi; Ishii, Masayuki; Yamano, Hiro-o; Sugita, Shintaro; Nakase, Hiroshi; et al.
Abstract: Introduction: Indocyanine green (ICG) fluorescence imaging has been used for blood flow assessment in anastomoses in the field of colorectal cancer surgery. However, whether ICG fluorescence is related to the presence of cancer cells in the lymph nodes is unclear. We explored the utilization of ICG fluorescence in colorectal cancer surgery. Materials and methods: ICG was injected into the submucosa around the tumor before radical resection in colorectal cancer patients. Intraoperatively, near-infrared (NIR) fluorescence was used for lymphatic flow visualization. After specimen removal, harvested lymph nodes were classified as positive or negative based on the detection of fluorescence, followed by pathological examination. ICG distribution on a section of each lymph node was examined by fluorescence microscopy. Results: Overall, 155 patients underwent real-time NIR fluorescence imaging-guided surgery. Altogether, 1, 017 lymph nodes were retrieved from these patients. Metastatic lymph nodes were present in 36 (5.8%) of 622 fluorescence-negative lymph nodes, which was significantly higher than 11 (2.8%) of 395 fluorescence-positive lymph nodes (odds ratio: 2.15, P  = 0.03). Fluorescence microscopy of metastatic lymph nodes showed that ICG fluorescence was present in the normal structural region but not in the cancerous region of the lymph nodes. Furthermore, ICG fluorescence was observed in all metastatic lymph nodes, except those with cancer cells occupying >90% of the total area. Conclusions: ICG fluorescence detected only the normal parts of the lymph node draining from the peritumoral area and not the cancer tissues. This finding is important for developing appropriate strategies for navigation surgery using NIR fluorescence.